MEDIA PEMBELAJARAN INTERAKTIF KULTUR JARINGAN TUMBUHAN DI SMA N 1 GRABAG DENGANADOBE ANIMATE CC 2015 - Estu Tunjung Pambayun; Sukris Sutiyatno; Kartika Imam Santoso (TRANSFORMASI, 2021)
The purpose of this research is to be able to design and build multimedia-based learning media in Biology lessons in plant tissue culture material so that it can be used as a learning tool to know more about plant tissue culture material using learning media.From these problems, the idea arose to create Biology Interactive Learning Media on Plant Tissue Culture Materials at SMA Negeri 1 Grabag.The research methodology used in this research is MDLC (Multimedia Development Life Cycle). The modeling used in this design is UML (Unified Modeling Language). System testing in this study uses Black Box Testing for testing application functional requirements, questionnaires for application testing, and Pre-Test Post-Test for material testing.Biology interactive learning media on plant tissue culture material has succeeded in becoming an interesting, effective, efficient source of student learning, as evidenced by the Pre-Test evaluation, there are still many students who have score below the KKM (70). After the Post-Test the student's score increases and it becomes above the KKM. Keywords:Biology, Plant Tissue Culture, MDLC, UML, Interactive